Cartilage Regeneration by Gene Therapy - Gelse, K.; Mark, K. von der; Schneider, H. (Current Gene Therapy, 2003)
Damage of articular cartilage is a frequent clinical problem and is commonly considered to be irreversible. Fullthickness defects may lead to the formation of fibrous repair tissue of minor mechanical quality, while partial-thickness lesions hardly show any repair response. Surgical approaches often fail to restore the articular surface, facing the problem of incomplete chondrogenesis or rapid degradation of the repair tissue. However, advances in molecular biology have revealed the potential of growth factors, differentiation factors, and cytokines in directing cellular differentiation and metabolic activity. Anabolic factors including members of the TGF-ß superfamily, IGF-1, FGF, or HGF have proven their potential to stimulate chondrogenesis and synthesis of cartilage-specific matrix components, allowing the formation of a hyaline cartilage-like repair tissue in experimental studies. In addition, anti-catabolic or anti-inflammatory molecules, such as IL-4, IL-10, IL-1Ra, and TNFsR may also exert beneficial effects by inhibiting excessive cartilage degradation. Although it is questionable whether regeneration of hyaline cartilage implying a complete restoration of the articular surface by a tissue that is identical with the original can ever be achieved, all these molecules have been considered as suitable tools for cartilage repair. The transfer of the respective genes into the joint, possibly in combination with the supply of chondroprogenitor cells, might be an elegant method to achieve a sustained delivery of such therapeutic factors at the required location in vivo. This review focuses on the therapeutic molecules, the suitability of different viral and nonviral vectors for intraarticular gene transfer and the lessons learned from gene therapy studies on various animal models.
Keywords: growth factor